Unemployment and market size - Ellison, M; Keller, G; Roberts, K; Stevens, M (Oxford University Press, 2013)
Without strong empirical support, labour market matching models typically assume constant returns to scale in matching. We construct a tractable equilibrium random matching model with a general matching technology, introducing market size effects: the job‐finding rate varies with unemployment. Stable steady‐states may occur in regions of increasing or decreasing returns, and multiple equilibria are welfare‐ranked by market size. While the standard model relies on high‐frequency shocks to the steady state to explain the co‐movement of unemployment and job‐finding, locally decreasing returns in matching generate plausible adjustment dynamics and slower convergence. Lastly, an extension of the Hosios condition internalises search externalities.